Effects of watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai var lanatus] leaf extracts on biological and histological paramaeters in type 2 diabetes rat model - Jibril, Muhammad Mustapha (2021)
Type 2 diabetes mellitus is a chronic metabolic disorder with multiple etiologies, causing complications leading to heart attack and even death in individuals when not well managed or untreated. Unfortunately, the available oral drug treatments have failed due to unwanted side effects, prompting the search for and use of natural remedies. This study aimed to investigate the antidiabetic effects of watermelon [Citrullus lanatus (Thunb.)] extracts in a high-fat diet-fed, streptozotocin (HFD/STZ)-induced diabetes rat model using proton nuclear magnetic resonance (1H NMR)-based metabolomics. Watermelon extracts were prepared from the flesh, rind and leaf, and extracted with 100%, 90%, 70%, 60%, 50% ethanol, and water. The extracts bioactivities were evaluated by α-amylase and α-glucosidase inhibition, and antioxidants assays, while their metabolites were profiled by 1H NMR spectroscopy. The extract with the highest bioactivity (60% leaf extract) was investigated in vivo for 6 weeks, using HFD-STZ diabetic rats combined with multiple low doses of streptozotocin. Serum and urine samples from the rats were profiled by 1H NMR spectroscopy and were analyzed for biochemical parameters. Moreover, the histopathological studies were done on their kidneys and liver by hematoxylin-eosin staining. Results showed that the IC50 for α-amylase inhibition of the 70% and 60% ethanol watermelon leaf extracts, were 42.0 ± 4.6 and 45.3 ± 2.2 μg/mL respectively, more potent than those of 60% ethanol rind, 59.5 ± 8.0 μg/mL and 60% ethanol flesh, 60.0 ± 3.3 μg/mL extracts. The IC50 for α-glucosidase inhibition of 60% ethanol leaf extract, 12.0 ± 0.2 μg/mL was more potent than those of 60% ethanol rind 24.7 ± 2.5 μg/mL, and flesh 23.0 ± 3.1 μg/mL extracts. The IC50 of 60% ethanol leaf extract, 51.9 ± 5.3 μg/mL for 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) radical inhibition was stronger than those of 60% the rind and flesh, 363.4 ± 16.3 and 487.4 ± 23.0 μg/mL respectively. The principal component analysis, partial least square discriminant analysis and biplots of the extracts showed that phenolic acids, epicatechin, isoeugenol, and citrulline could be responsible for the most potent α-amylase and α-glucosidase inhibition, and antioxidant effects of the leaf extracts. Six-week treatment with high dose (400 mg/kg body weight) of 60% ethanol watermelon leaf extract reduced the fasting blood sugar, serum insulin, and total cholesterol of diabetic rats. Also, serum antioxidant enzymes activities were increased and normalized, with high dose watermelon leaf extract better than the standard drug (Metformin). Histopathological examination of kidneys and liver revealed tubular necrosis and hyaline cast formation in the diabetic rats’ kidneys, necrosis and hepatocytes leucocyte infiltration, which were also restored back to normal after the treatment period. Metabolomics studies on the serum and urine revealed increased metabolic markers of the perturbed carbohydrate, amino acids and lipid pathways in the diabetic rats. Dysregulated pathways were gradually brought back to normal in a slow pace. The high dose watermelon leaf extract also had better results in restoring the perturbed pathways than the standard, indicating that 60% ethanol watermelon leaf extract could be as potent as metformin. This study predicted that watermelon leaf may have more potent antidiabetic lead molecules than metformin when explored. Therefore, watermelon leaf could serve as a potential raw material for functional foods and nutraceuticals ingredients for the management of type 2 diabetes mellitus.